2018
DOI: 10.1016/j.ajpath.2018.08.015
|View full text |Cite
|
Sign up to set email alerts
|

The Amount of Bifidobacterium Genus in Colorectal Carcinoma Tissue in Relation to Tumor Characteristics and Clinical Outcome

Abstract: Evidence indicates a complex link between microbiota, tumor characteristics, and host immunity in the tumor microenvironment. In experimental studies, bifidobacteria appear to modulate intestinal epithelial cell differentiation. Accumulating evidence suggests that bifidobacteria may enhance the antitumor immunity and efficacy of immunotherapy. We hypothesized that the amount of bifidobacteria in colorectal carcinoma tissue might be associated with tumor differentiation and higher immune response to colorectal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 79 publications
3
49
0
1
Order By: Relevance
“…In contrast, the members of Bifidobacterium genus have been considered to inhibit colorectal carcinogenesis through the prevention of enteropathogenic infection and the inhibition of secondary bile acid production [46][47][48]. Our previous population-based study has shown that intratumoural Bifidobacterium genus may reflect loss of intestinal barrier function in poorly differentiated colorectal cancer [36]. These distinct characteristics of F. nucleatum and Bifidobacterium genus are supported by our results of differing associations with autophagic activity.…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, the members of Bifidobacterium genus have been considered to inhibit colorectal carcinogenesis through the prevention of enteropathogenic infection and the inhibition of secondary bile acid production [46][47][48]. Our previous population-based study has shown that intratumoural Bifidobacterium genus may reflect loss of intestinal barrier function in poorly differentiated colorectal cancer [36]. These distinct characteristics of F. nucleatum and Bifidobacterium genus are supported by our results of differing associations with autophagic activity.…”
Section: Discussionsupporting
confidence: 85%
“…Bifidobacteria possibly acts as a protective probiotic in CRC, acting by enhancing intestinal epithelial homeostasis [ 137 ]. Kosumi et al [ 138 ] assessed the prognostic potential of Bifidobacterium in a cohort study of 1313 CRC patients. Contrary to the above findings, they reported the detection of Bifidobacterium in 30% of tumors with no statistically significant association between its abundance and survival outcomes or molecular and clinicopatholigical features of CRC.…”
Section: Intestinal Microbiota and Long-term Outcomes Following Crmentioning
confidence: 99%
“…These studies provide population‐based evidence for the potential role of the microbiome in mediating the relationship between diet and colorectal carcinogenesis. Studies support the roles of viruses and other bacteria, such as enterotoxigenic Bacteroides fragilis , pks‐positive Escherichia coli , Enterococcus faecalis , Lactobacillus , and Bifidobacterium in colorectal cancer . Therefore, investigation of these bacteria and a microbial community as a whole in relation to the incidence and progression of colorectal cancer is also warranted.…”
Section: Study Examples and Proposalsmentioning
confidence: 99%